2022
DOI: 10.3892/etm.2022.11146
|View full text |Cite
|
Sign up to set email alerts
|

Metformin reduces chondrocyte pyroptosis in an osteoarthritis mouse model by inhibiting NLRP3 inflammasome activation

Abstract: Osteoarthritis (OA) is an age-related degenerative disease, and its incidence is increasing with the ageing of the population. Metformin, as the first-line medication for the treatment of diabetes, has received increasing attention for its role in OA. The purpose of the present study was to confirm the therapeutic effect of metformin in a mouse model of OA and to determine the mechanism underlying the resultant delay in OA progression. The right knees of 8-week-old C57BL/6 male mice were subjected to destabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…Mice were injected intra-articularly with Erastin (15 mg/kg) [ 38 ], and the sham and DMM groups were injected with an equal volume of saline twice a week. Moreover, Met was administered by gavage (200 mg/kg/day) [ 23 ]. Mice were killed by overdose anesthesia 8 weeks after surgery, and the right knee joint was collected for subsequent experiments.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mice were injected intra-articularly with Erastin (15 mg/kg) [ 38 ], and the sham and DMM groups were injected with an equal volume of saline twice a week. Moreover, Met was administered by gavage (200 mg/kg/day) [ 23 ]. Mice were killed by overdose anesthesia 8 weeks after surgery, and the right knee joint was collected for subsequent experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Subchondral osteosclerosis is an important pathological marker of OA [ 22 ]. The results of our previous study demonstrated that a mouse OA model induced by surgery developed late pathological changes with subchondral osteosclerosis 8 weeks after surgery [ 23 , 24 ]. The specific mechanisms underlying subchondral osteosclerosis in advanced stages of OA remain to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study investigating the association between MET use and disease progression in obese people with knee OA found that MET use was significantly associated with lower rates of medial cartilage volume loss, indicating that MET may have protective effects on knee OA progression in people without diabetes mellitus [ 16 ]. Moreover, basic scientific studies focusing on the effects of MET on experimental OA mice models also indicated that MET may have a protective effect on OA in non-diabetic subjects [ 11 , 13 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that OA rats receiving MET treatment had a better pain tolerance, suggesting that MET may attenuate OA development and progression [ 11 ]. Furthermore, some basic research studies have reported that MET may alleviate OA via attenuating osteoclast-mediated abnormal subchondral bone remodeling, reducing chondrocyte pyroptosis, and inhibiting chondrocyte ferroptosis [ 12 , 13 , 14 ]. In addition, these pleiotropic effects of MET have been described to occur mainly through activating the adenosine monophosphate-activated protein kinase (AMPK) pathway [ 11 ].…”
Section: Introductionmentioning
confidence: 99%